Performance, subjectivity, and experimentation - Laws, Catherine ca. 20. Jh (Leuven University Press, 2020)
Music reflects subjectivity and identity: that idea is now deeply ingrained in both musicology and popular media commentary. The study of music across cultures and practices often addresses the enactment of subjectivity "in" music - how music expresses or represents ?an? individual or ?a? group. However, a sense of selfhood is also formed and continually reformed through musical practices, not least performance. How does this take place? How might the work of practitioners reveal aspects of this process? In what sense is subjectivity performed in and through musical practices? This book explores these questions in relation to a range of artistic research involving contemporary musical practices, drawing on perspectives from performance studies, phenomenology, embodied cognition, and theories of gendered and cultural identity.
Keywords: Performance -- Künste; Künstlerische Forschung; Subjektivität; Identität; Subjectivity in music; ART / Performance; Aufsatzsammlung